2021
DOI: 10.3390/ijms221910593
|View full text |Cite
|
Sign up to set email alerts
|

Esterase Activity of Serum Albumin Studied by 1H NMR Spectroscopy and Molecular Modelling

Abstract: Serum albumin possesses esterase and pseudo-esterase activities towards a number of endogenous and exogenous substrates, but the mechanism of interaction of various esters and other compounds with albumin is still unclear. In the present study, proton nuclear magnetic resonance (1H NMR) has been applied to the study of true esterase activity of albumin, using the example of bovine serum albumin (BSA) and p-nitrophenyl acetate (NPA). The site of BSA esterase activity was then determined using molecular modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Apart from UV–vis studies, we have characterized the final product, para -nitrophenolate, using time-dependent nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry, and the results are in line with literature reports (Figures S9 and S10). Interestingly, we observed that, with the addition of 20 mM CHAPS/NaC/NaDC to the Fe-hTF/CTAB system, the reaction kinetics of the esterase-like activity of Fe-hTF was extremely attenuated, and no appreciable catalysis was observed as evident from their nonvariant absorption kinetic traces (Figures b,c and S11a–c). Several control experiments have also been performed to unveil the predominant role of CTAB in accelerating the reaction kinetics of the esterase-like activity of the protein, as demonstrated in Figure S12a,b.…”
Section: Resultsmentioning
confidence: 93%
“…Apart from UV–vis studies, we have characterized the final product, para -nitrophenolate, using time-dependent nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry, and the results are in line with literature reports (Figures S9 and S10). Interestingly, we observed that, with the addition of 20 mM CHAPS/NaC/NaDC to the Fe-hTF/CTAB system, the reaction kinetics of the esterase-like activity of Fe-hTF was extremely attenuated, and no appreciable catalysis was observed as evident from their nonvariant absorption kinetic traces (Figures b,c and S11a–c). Several control experiments have also been performed to unveil the predominant role of CTAB in accelerating the reaction kinetics of the esterase-like activity of the protein, as demonstrated in Figure S12a,b.…”
Section: Resultsmentioning
confidence: 93%
“…PNPA, a classical substrate of carboxylesterase, is widely used to study the esterase activity of serum albumins. Usually, the protein hydrolyzes PNPA to produce yellow-colored p -nitrophenol, which can easily be detected by monitoring the absorbance at 400 nm. , On increasing concentration of NaDC, the esterase activity of both BSA and HSA was found to decrease, suggesting the effect of NaDC on the native structure of the serum albumins (Figure ). In a recent study, Belinskaia et al have proposed that Tyr149 in Sudlow site I of BSA (Tyr150 for HSA) is actively involved in the esterase activity of the serum albumins .…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the protein hydrolyzes PNPA to produce yellow-colored p -nitrophenol, which can easily be detected by monitoring the absorbance at 400 nm. , On increasing concentration of NaDC, the esterase activity of both BSA and HSA was found to decrease, suggesting the effect of NaDC on the native structure of the serum albumins (Figure ). In a recent study, Belinskaia et al have proposed that Tyr149 in Sudlow site I of BSA (Tyr150 for HSA) is actively involved in the esterase activity of the serum albumins . Therefore, the decrease in the esterase activity of these proteins in the presence of NaDC can be attributed to the alteration in the microenvironment of the tyrosines by NaDC, which has also been observed from SFS studies.…”
Section: Resultsmentioning
confidence: 99%
“…47 The binding energies of polystyrene and paracetamol were equal only at Sudlow site II. 26 Even though the binding energies were the same, this might not be the case for larger polystyrene molecules such as NPS. The NPS has thousands of polystyrene molecules that can interact with multiple residues at the same time, causing even stronger binding.…”
Section: Molecular Dockingmentioning
confidence: 97%
“…A docking study was performed using AutoDock 1.5.6. 26 The protein molecule was prepared for docking by the deletion of water, followed by the addition of Kollman charges and hydrogens. The ligand and protein molecules were saved as pdbqt files.…”
Section: Molecular Dockingmentioning
confidence: 99%